2022
DOI: 10.1111/jcpe.13614
|View full text |Cite
|
Sign up to set email alerts
|

Association between bleeding periodontal pockets and eczemas: Results of the Northern Finland Birth Cohort 1966

Abstract: Aim To investigate whether the periodontal condition as measured by bleeding periodontal pockets is associated with atopic dermatitis, seborrheic dermatitis, and eczema nummulare. Materials and Methods The study population (n = 1871) was obtained from the 46‐year follow‐up study of the Northern Finland Birth Cohort 1966 study (NFBC1966). The periodontal condition was measured by the number of sites with bleeding periodontal pockets that were ≥4 mm deep. The whole skin of the participants was clinically examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
0
1
Order By: Relevance
“…Furthermore, there is a report showing no positive association between atopic dermatitis and periodontitis. 21 The present study also showed no positive association between discontinuation of dental treatment and exacerbation of atopic dermatitis. Moreover, no positive association between discontinuation of dental treatment and exacerbation of mental illness, such as depression, was similarly shown.…”
Section: Cariogenic Bacteria and Systemic Diseasecontrasting
confidence: 57%
“…Furthermore, there is a report showing no positive association between atopic dermatitis and periodontitis. 21 The present study also showed no positive association between discontinuation of dental treatment and exacerbation of atopic dermatitis. Moreover, no positive association between discontinuation of dental treatment and exacerbation of mental illness, such as depression, was similarly shown.…”
Section: Cariogenic Bacteria and Systemic Diseasecontrasting
confidence: 57%